Reflections of Vietnamese English Language Educators on Their Writer Identities in English and Vietnamese. Issue 3 (3rd May 2020) - Starks, Donna; Nicholas, Howard
ABSTRACT: In today's globalised world, options have increased for how people write. Individuals who write in an additional language draw on their varied language learning experiences, their study and travel abroad, as well as their interactions with colleagues and friends in the institutions in which they work. While some features of texts produced in English as a Foreign Language (EFL) contexts may initially appear to be simple appropriations of English as a Native Language (ENL) features, deeper investigations into how writers report on their writing practices reveal richer and more complex perceptions of the writer's self. In this article, we explore how Vietnamese English language educators report on their own writing and how they teach others to write in order to show the complex and diverse ways in which these Vietnamese educators view their English and Vietnamese academic writing practices and enact their writer identities.